Depth partitioning of mesophotic reef fish communities on Pickle Bank seamount - Jack V. Johnson; Alex D. Chequer; Gretchen Goodbody-Gringley (Frontiers in Marine Science, 2025)
Mesophotic coral ecosystems (MCEs)—reefs below 30m depth—represent distinct ecological communities that are under threat from local (e.g., fishing) and global (e.g., climate change) disturbances. However, most MCEs remain unexplored, and their ecological communities are not well characterized. MCEs on remote offshore seamounts are further unexplored and provide the opportunity to assess assembly rules from comparatively less disturbed MCEs, given their remoteness from settlements with high human population densities. Here, we characterize the fish community from the remote offshore seamount of Pickle Bank in the Central Caribbean Sea, exploring differences in the fish community at a 25m depth compared to the mesophotic zone at a 45m depth. We found differences in species composition between the depths, with a significantly higher abundance of fish at mesophotic depths, while species diversity and species richness were significantly higher at the shallow sites. Species from Labridae and Scaridae dominated the biomass at the shallow sites, while species in the family Carangidae dominated biomass in the mesophotic zone. There were also differences in the community composition of trophic guilds between depths, with higher macrocarnivore biomass, macrocarnivore abundance, and omnivore abundance at deep sites compared to shallow sites. Despite the logistical challenges and limitations associated with accessing MCEs on offshore seamounts, these data provide compelling evidence to the growing body of literature documenting MCEs as unique habitats warranting further data collection to obtain a holistic understanding of shallow and mesophotic seamount ecosystems.